2016
DOI: 10.1186/s12885-015-2011-5
|View full text |Cite
|
Sign up to set email alerts
|

The lack of clinical value of peritoneal washing cytology in high risk patients undergoing risk-reducing salpingo-oophorectomy: a retrospective study and review

Abstract: BackgroundTo assess the clinical value of peritoneal washing cytology (PWC) in women with BRCA1 or BRCA2 mutations and women from a family with hereditary breast and/or ovarian cancer (HBOC) undergoing risk-reducing salpingo-oophorectomy (RRSO) in detecting primary peritoneal cancer (PPC) or occult ovarian/fallopian tube cancer.MethodsA retrospective study of patients with known BRCA1 or BRCA2 mutation or HBOC who underwent RRSO at the Erasmus Medical Centre, Rotterdam, The Netherlands between January 2000–201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Three (4.5%) of 67 patients with follow‐up records showed subsequent primary peritoneal cancer during the follow‐up period. The clinical significance of positive peritoneal cytology at RRSO also remains unclear, and it has not been determined whether positive cytology is associated with a higher risk of subsequent peritoneal cancer . Furthermore, there is insufficient evidence that surgical staging or postoperative chemotherapy for patients with isolated STIC at RRSO decreases the occurrence of peritoneal cancer.…”
Section: How To Deal With Isolated Stic Detected At Rrso?mentioning
confidence: 99%
“…Three (4.5%) of 67 patients with follow‐up records showed subsequent primary peritoneal cancer during the follow‐up period. The clinical significance of positive peritoneal cytology at RRSO also remains unclear, and it has not been determined whether positive cytology is associated with a higher risk of subsequent peritoneal cancer . Furthermore, there is insufficient evidence that surgical staging or postoperative chemotherapy for patients with isolated STIC at RRSO decreases the occurrence of peritoneal cancer.…”
Section: How To Deal With Isolated Stic Detected At Rrso?mentioning
confidence: 99%
“…However, outcomes among patients with positive PWC (malignant or suspicious for malignancy) without pathologically identified malignancy or precancerous lesions have not been reported frequently. In the literature, 11 patients have had positive PWC with no macroscopic malignancies found during RRSO (Table 2) [1014]. The frequency of cases with no macroscopic findings consistent with malignancy but with positive PWC is about 1%, which is not low.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether or not pelvic washing cytology should be performed at RRSO is controversial. Blok et al reported that malignant washing cytology samples fail to add value to histopathological examinations for the detection of ovarian and/or fallopian tube cancer using the SEE-FIM protocol [14].…”
Section: Discussionmentioning
confidence: 99%